Checklist of mangrove snails (Mollusca: Gastropoda) in South Coast of Pamekasan, Madura Island, East Java, Indonesia - R Adharyan Islamy; Veryl Hasan (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Islamy RA, Hasan V. 2020. Checklist of mangrove snails (Mollusca: Gastropoda) in South Coast of Pamekasan, Madura Island, East Java, Indonesia. Biodiversitas 21: 3127-3134. Mangrove forests are crucial to gastropods providing breeding and nursery grounds, food sources, and shelter from predators. They are useful bioindicators of environmental pollution. Consequently, it is crucial to understand the species richness of gastropods mangrove environments. This study aims to provide information about the species composition of mangrove snails in the South Coast of Pamekasan (Madura Island), East Java, Indonesia. Samplings were performed at low tide from 4 stations in December 2019 using a transect (10m x 10m). All samples were identified using reference books and published journal. We found a total of 10 family consist of Assimineidae, Cerithiidae, Ellobiidae, Littorinidae, Muricidae, Neritidae, Olividae, Planaxidae, Potamididae, and Trochidae with consist of 15 Genus, i.e., Assiminea, Clypeomorus, Cerithium, Rhinoclavis, Laemodonta, Littorarina, Tenguella, Semiricinula, Nerita, Clithon, Oliva, Planaxis, Pirenella, Telescopium, and Monodonta. The most common substrate where mangrove snails were found was rocks, sandy, and around the tree and roots of mangrove. All gastropods in this study found alive during our surveys and predominantly mangrove associated. We assume that there are still many snails that have not been surveyed at the location. We suggest to the future researcher to survey through different sampling efforts and sampling methods such as quantitative or semi-quantitative methods.